The Roles of Academic Self-Efficacy and Intolerance of Uncertainty on Decisional Procrastination in University Students during the COVID-19 Pandemic - Elisabetta Sagone; Maria Luisa Indiana (MDPI AG, 2023)
Decisional procrastination has been one of the main phenomena analysed in university students, together with self-efficacy, during the COVID-19 pandemic. We examined the roles of academic self-efficacy and intolerance of uncertainty on decisional procrastination in 318 Italian university students. Furthermore, the mediating role of the intolerance of uncertainty on the relationships between academic self-efficacy and decisional procrastination was explored. The Academic Self-Efficacy Scale, the Decisional Procrastination Scale, and the Intolerance of Uncertainty Scale were used. Results: Decisional procrastination was predicted by the components of academic self-efficacy and the intolerance of uncertainty (prospective and inhibitory intolerance). Furthermore, the mediating role of the prospective intolerance of uncertainty was confirmed in the relationship between self-efficacy (self-engagement and self-oriented decision-making) and decisional procrastination. Conclusions: This study adds new evidence to findings in the analysis of the role of the intolerance of uncertainty in mitigating the relationships between the self-efficacy of students in the academic context and their tendency to procrastinate in decision-making processes, which has been poorly investigated to date by scholars in this research field. Future research will deal with a specific situation of procrastinating behaviours, such as the completion of a master's thesis or the respect for the deadline of an article's submission.